Prenatal predictors of objectively measured appetite regulation in low‐income toddlers and preschool‐age children. Issue 11 (18th June 2019) - Boone‐Heinonen, Janne; Weeks, Heidi M.; Sturza, Julie; Miller, Alison L.; Lumeng, Julie C.; Bauer, Katherine W.
Summary: Background: Prenatal nutrition impacts offspring appetite regulation in animal models. However, evidence from humans is scarce. Objective: To determine associations between indicators of prenatal nutrition and appetite regulation among young children. Methods: Participants included 454 low‐income mother/child dyads (mean child age = 45.2 months [SD = 9.7]). Children's appetite regulation was ascertained with the maternal‐reported Child Eating Behavior Questionnaire and objectively assessed using the Eating in the Absence of Hunger protocol. Using hierarchical linear regression, we modelled child appetite regulation measures as a function of prenatal nutrition indicators (child birthweight z scores [BWz, BWz 2 ]; maternal pre‐pregnancy body mass index [BMI], gestational weight gain [GWG]), adjusted for sociodemographic characteristics. Results: Among girls, higher and lower birthweight were associated with greater energy consumed in the absence of hunger, primarily sweet foods, coeff (95% CI): BWz 0.17 (0.05, 0.28), BWz 2 0.15 (0.04, 0.26), but not food responsiveness or food enjoyment. Higher birthweight was also associated with greater satiety responsiveness among girls. Among boys, birthweight was unrelated to measures of appetite regulation. Associations between maternal BMI and GWG and child appetite regulation were inconsistent. Conclusions: Among low‐income girls, but not boys, indicators of adverse prenatal conditions were associated with poor objectively measured appetite regulation during early childhood.